ZigBee–based long–thin wireless sensor networks: address assignment and routing schemes. (4th March 2013) - Pan, Meng–Shiuan; Tseng, Yu–Chee
Although Wireless Sensor Networks (WSNs) have been extensively researched, its deployment is still a big concern. This paper makes two contributions to this issue. First, we promote a new concept of Long–Thin (LT) topology for WSNs, where a network may have a number of linear paths of nodes as backbones connecting to each other. These backbones are to extend the network to the intended coverage areas. At the first glance, a LT WSN only seems to be a special case of numerous WSN topologies. However, we observe, from real deployment experiences, that such a topology is quite general in many applications and deployments. The second contribution is that we show that the address assignment and thus the tree routing scheme defined in the original ZigBee specification may work poorly, if not fail, in a LT topology. We then propose simple, yet efficient, address assignment and routing schemes for a LT WSN. Simulation results are reported.